Heterobimetallic alkaline earth metal–metal bonding - Mai, Jonathan; Maurer, Johannes; Langer, Jens; Harder, Sjoerd (Nature Synthesis, 2023)
Low-oxidation-state complexes of type (BDI)Mg–Mg(BDI) (BDI, β-diketiminate) show broad reactivity, finding application as soluble, universal reducing agents, enriching the field of early main group metal chemistry. Attempts to isolate similar, but considerably more reactive, Ca–Ca bound complexes have so far failed. As the metal–metal bond strength descending group 2 rapidly decreases, BDI complexes of the heavier AeI (alkaline earth) ions (Ae = Ca, Sr, Ba) probably exist as (BDI)Ae· radicals of untamed reactivity. Here we describe a facile method to prepare stable but highly reactive complexes with heterobimetallic Mg–Ae bonds. Mixing [(BDI)MgˉNa+]2 and [Ae(NR2)2]2 dimers led to anion–cation exchange and exclusive formation of mixed species: (BDI)MgˉNa+/Ae(NR2)2 (Ae = Ca, Sr, Ba; R = SiMe3). Crystal structures feature examples of Mg–Ca and Mg–Sr bonding with formal oxidation states of Mg0–AeII. Best described as polarized Mgδˉ–Aeδ+ bonds, these complexes show potential as alkane-soluble reductants for bond activation, which readily react with benzene by C–H bond cleavage and are oxidized to discrete complexes with N2O. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-12-15